The effects of non-nutritive sweeteners on energy and macronutrients intake in adults: a grade-assessed systematic review and meta-analyses of randomized controlled trials - Rostampour, Kimia; Moghtaderi, Fatemeh; Najafi, AmirHossein; Seyedjafari, Behnaz; Salehi-Abargouei, Amin (Frontiers in Nutrition, 2024)
Objectives: The effect of non-nutritive sweeteners (NNSs) on long-term satiety is not well understood. This systematic review and meta-analysis were performed to investigate the effect of NNSs on long-term total energy and macronutrients intake. Methods: Online databases including Scopus, PubMed, ISI Web of Science, and Google Scholar were searched up to September 2024 to find relevant randomized control trials (RCTs). A random effects model was used for estimating the overall effects. Results: The results showed a reducing effect of NNSs consumption vs. sugar on total energy intake [total energy intake change = -175.26 kcal/day, 95% confidence interval (CI): -296.47 to -54.06, I2 = 61.19%] and carbohydrate intake [Hedges’ g = -0.35, 95% CI: -0.63 to -0.06, I2 = 58.99%]. While, NNSs intake vs. water was not associated with significant change in total energy intake [total energy intake change = 29.94 kcal/day, 95% CI: -70.37 to 130.24, I2 = 34.98%] and carbohydrate intake [Hedges’ g = 0.28, 95% CI: -0.02 to 0.58, I2 = 65.26%]. The Consumption of NNSs compared to the either sugar or water did not have a significant effect on fat intake [Hedges’ g sugar = 0.08, 95% CI: -0.10 to 0.26, I2 =8.73%/ Hedges’ g water = 0.20 g/day, 95% CI: -3.48 to 3.88, I2 = 0%] and Protein intake [Hedges’ g sugar = 0.16, 95% CI: -0.11 to 0.42, I2 = 50.83%/Hedges’ g water = 0.00, 95% CI: -0.15 to 0.16, I2 = 0%]. Conclusion: In summary, our findings suggest that NNSs consumption may be effective in reducing total energy and carbohydrate intake compared to sugar.